Coiled-Coil Domain of Enteropathogenic Escherichia coli Type III Secreted Protein EspD Is Involved in EspA Filament-Mediated Cell Attachment and Hemolysis - Daniell, Sarah J. (American Society for Microbiology, 2001)
Many animal and plant pathogens use type III secretion systems to secrete key virulence factors, some directly into the host cell cytosol. However, the basis for such protein translocation has yet to be fully elucidated for any type III secretion system. We have previously shown that in enteropathogenic and enterohemorrhagic Escherichia coli the type III secreted protein EspA is assembled into a filamentous organelle that attaches the bacterium to the plasma membrane of the host cell. Formation of EspA filaments is dependent on expression of another type III secreted protein, EspD. The carboxy terminus of EspD, a protein involved in formation of the translocation pore in the host cell membrane, is predicted to adopt a coiled-coil conformation with 99% probability. Here, we demonstrate EspD-EspD protein interaction using the yeast two-hybrid system and column overlays. Nonconservative triple amino acid substitutions of specific EspD carboxy-terminal residues generated an enteropathogenic E. coli mutant that was attenuated in its ability to induce attaching and effacing lesions on HEp-2 cells. Although the mutation had no effect on EspA filament biosynthesis, it also resulted in reduced binding to and reduced hemolysis of red blood cells. These results segregate, for the first time, functional domains of EspD that control EspA filament length from EspD-mediated cell attachment and pore formation.